2015
DOI: 10.1111/bdi.12326
|View full text |Cite
|
Sign up to set email alerts
|

Symptom severity, self‐reported adherence, and electronic pill monitoring in poorly adherent patients with bipolar disorder

Abstract: Objectives This analysis of screening and baseline data from an ongoing trial examined self-report versus automated adherence monitoring and assessed the relationship between bipolar disorder (BD) symptoms and adherence in 104 poorly adherent individuals. Methods Adherence was measured with the Tablets Routine Questionnaire (TRQ) and the Medication Event Monitoring System (MEMS). Symptoms were measured with the Montgomery–Åsberg Depression Rating Scale (MADRS), the Young Mania Rating Scale (YMRS), and the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
2
19
1
1
Order By: Relevance
“…Furthermore, a larger number of medications may be a reflection of increased severity of illness. The finding that more severe bipolar disorder symptoms are associated with worse adherence has also been reported by others (Barraco, Rossi, Nicolò, & Group, 2012; Leclerc et al, 2013; Sajatovic et al, 2015) and does not seem surprising given the likelihood that symptoms of both depressive episodes such as lack of motivation and symptoms of manic episodes including distractibility and lack of focus could both impede an individual’s ability to take medications on a regular basis.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, a larger number of medications may be a reflection of increased severity of illness. The finding that more severe bipolar disorder symptoms are associated with worse adherence has also been reported by others (Barraco, Rossi, Nicolò, & Group, 2012; Leclerc et al, 2013; Sajatovic et al, 2015) and does not seem surprising given the likelihood that symptoms of both depressive episodes such as lack of motivation and symptoms of manic episodes including distractibility and lack of focus could both impede an individual’s ability to take medications on a regular basis.…”
Section: Discussionsupporting
confidence: 74%
“…Correlates of poor adherence to psychiatric medication in individuals with bipolar disorder include denial of illness, symptom severity, cognitive impairment, side effects, lack of illness knowledge, disorganized home environment, lack of social support, problems accessing treatment, and comorbid substance abuse (Clatworthy, Bowskill, Rank, Parham, & Horne, 2007; Hou, Cleak, & Peveler, 2010; Levin, Tatsuoka, Cassidy, Aebi, & Sajatovic, 2015; Pompili et al, 2013; Sajatovic et al, 2011; Sajatovic et al, 2015). Recent reviews also identify several sociodemographic correlates of poor adherence to bipolar disorder medications.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the BMS program improved medication adherence among Taiwanese Han-Chinese with BP-II. Medication adherence is crucial for long-term illness management, and nonadherence is considered one of the most challenging problems when treating patients with BP [25,26]. Of the interventions for improving adherence, psychoeducation has shown longlasting prophylactic effects in patients with BP [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors are associated with unsatisfactory treatment of depression in both MDD and BD (table 2). These include probable limitations of the effectiveness of available treatments but also less than vigorous treatment and inconsistent treatment adherence, especially long-term when acute symptoms are no longer present [5,54,55,56,57]. The use of even moderate doses of antidepressants for more than a few weeks is not easily achieved, and such inadequate treatment surely contributes to apparent ‘treatment resistance' and on inclination to try new or added treatments [58,59,60,61].…”
Section: Risk Factors For Poor Outcomementioning
confidence: 99%
“…Typically limited antidepressant responses in BD as well as in MDD often lead to polytherapy, with multiple medicines given in combinations that are usually inadequately evaluated for additional efficacy and safety, with higher burdens of adverse effects and cost [5,6,57,60]. In addition to the overuse of antidepressants and complex treatment regimens encouraged by incomplete clinical responses in mood disorders (often after inadequate trials of monotherapies), erratic treatment adherence involves repeated discontinuation and restarting [56,57]. …”
Section: Risk Factors For Poor Outcomementioning
confidence: 99%